A Research Note on the Situational Contexts of Inter-Ethnic “Stand Your Ground” Incidents - Albert E. McCormick Jr. (Journal of Public and Professional Sociology, 2017)
Analysis of 311 Florida’s Stand Your Ground (SYG) cases found no significant differences in SYG defense success in inter-ethnic incidents, a result apparently contradictory to some other SYG research. Any disparities in SYG inter-ethnic situations seem based upon, not racial bias, but such situational factors as the nature of pre-incident inter-personal relationships, the incident’s location and trigger, and whether the alleged assailant was armed and/or committing a crime during the incident.